Pengaruh Debt To Equity Ratio, Current Ratio, Cash Ratio, Return On Asset Dan Total Asset Turnover Terhadap Dividend Payout Ratio Pada Perusahaan Basic Materials - Kartika Chandra; Meilia Tan; Dianty Putri Purba; Yunita Sari Rioni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study is to examine how the influence of Debt to Equity Ratio, Current Ratio, Cash Ratio, Return on Asset and Total Asset Turnover on Dividend Payout Ratio in Basic Materials sector companies for the period 2018-2021. The technique applied is purposive sampling. The population used for 4 years. The data source used in this study is the official website of the Indonesia Stock Exchange. This study uses SEM-PLS (Structural Equation Modeling-Partial Least Square) analysis assisted by the SmartPLS 4.0 program. The results of this study show that Debt to Equity Ratio and Current Ratio affect the Dividend Payout Ratio, while Cash Ratio, Return on Asset and Total Asset Turnover have no effect on Dividend Payout Ratio. Keywords: Debt to Equity Ratio, Current Ratio, Cash Ratio, Return on Asset, Total Asset Turnover, Dividend Payout Ratio.